The Implementation of PSAK 409 Technology-Based Accounting on the Quality of Financial Statements in Zakat Management Organizations - Dicky Rivawandar; Ibrahim Rozin; Efri Syamsul Bahri (Journal of Social Research, 2026)
Zakat Management Organizations (OPZs) play an important role in managing public funds, requiring high levels of transparency, accountability, and reliable financial reporting. However, many OPZs continue to face challenges in implementing PSAK 409 consistently due to limited accounting capabilities and inadequate financial information systems. The advancement of digital technology provides opportunities to improve accounting processes through automated, integrated, and standardized reporting systems. This study aimed to examine the effect of technology-based accounting implementation on financial statement quality and PSAK 409 compliance in Zakat Management Organizations. This research employed a quantitative approach with a descriptive causal design. Data were collected through questionnaires distributed to OPZ managers and analyzed using validity and reliability tests, linear regression analysis, and hypothesis testing with statistical software. The results indicated that technology-based accounting implementation had a positive and significant effect on financial statement quality by improving the accuracy, relevance, reliability, and timeliness of financial information. Furthermore, technology adoption strengthened PSAK 409 compliance by supporting standardized recording procedures and reducing the risk of human errors in zakat financial management. The findings demonstrated that accounting technology functioned not only as an operational tool but also as an internal control mechanism that enhanced organizational accountability. This study concluded that digital transformation in accounting systems was essential for improving transparency, professionalism, and governance quality in Zakat Management Organizations.